Introducing “Kembang Matahari” Noodle Crackers as Regional Specialty Products to the Global Market through Packaging Design - Dendi Pratama; iis Purnengsih; Nurulfatmi Amzy; Pandu Pramudita (JURNAL PengaMAS, 2021)
The regional specialty products based on local identity is a government program that is intended to introduce products unique to the region to be sold to the market. Regional specialty products have a potent value because they can incorporate local identities that can penetrate global markets. Noodle Crackers is one of the specialty products originated in the region of Bogor, specifically in the Karadenan village. The conventional marketing, meaning that it is only distributed to Greater Jakarta areas, makes Noodle Crackers only to be produced during the fasting month of Ramadhan. Aside of that, the production decreases annually due to the lack of interest in the market outside of the fasting month. This resulted in the sale of Bogor Noodle Crackers to tank and affecting the production capacity, decreasing the revenue further every year even though the export market is a potential market for this Noodle Crackers. This paper discusses the effort in introducing the Noodle Crackers, specifically the “Kembang Matahari” brand, in order to bring the global market’s attention using a qualitative approach. The effort includes the logo and packaging design for Noodle Crackers as a part of its distinct visual identity within the global market. The results shown in this paper are the logo and the packaging meticulously designed for Noodle Crackers to prepare this regional specialty product in entering the export market, becoming one of the reliable international businesses in the Karadenan Village, Bogor.